2017
DOI: 10.1002/jbt.21932
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Epigallocatechin-3-gallate inhibits human angiotensin-converting enzyme activity through an autoxidation-dependent mechanism

Abstract: We investigated the molecular mechanisms involved in the angiotensin-converting enzyme (ACE) inhibition by (-)-epigallocatechin-3-gallate (EGCg), a major tea catechin. EGCg inhibited both the ACE activity in the lysate of human colorectal cancer cells and human recombinant ACE (rh-ACE) in a dose-dependent manner. Co-incubation with zinc sulfate showed no influence on the rh-ACE inhibition by EGCg, whereas it completely counteracted the inhibitory effect of ethylenediaminetetraacetic acid, a chelating-type ACE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A mechanism for the autoxidation of EGCG was based on the formation of EGCG quinone, EGCG dimer quinone, and other related compounds [ 70 ]. For example, EGCG can inhibit the angiotensin-converting enzyme (ACE) activity through oxidation into an electrophilic quinone [ 71 ], which may be related to the treatment of cardiovascular diseases. Moreover, the formation of autoxidized products also contributes to the inhibition of fibrillation [ 72 ].…”
Section: The Basic Properties Of Egcgmentioning
confidence: 99%
“…A mechanism for the autoxidation of EGCG was based on the formation of EGCG quinone, EGCG dimer quinone, and other related compounds [ 70 ]. For example, EGCG can inhibit the angiotensin-converting enzyme (ACE) activity through oxidation into an electrophilic quinone [ 71 ], which may be related to the treatment of cardiovascular diseases. Moreover, the formation of autoxidized products also contributes to the inhibition of fibrillation [ 72 ].…”
Section: The Basic Properties Of Egcgmentioning
confidence: 99%
“…2 ; supplementary file, S-table1). This binding was compared with some known/reported binder epigallocatechin-3-gallate(EGCG) [ 19 ]; −4.53 kcal/mol with ki 479.87 μmol and Theaflavin gallate [TFDG]; −2.85 kcal/mol with ki value 8.2 μmol. Best ten binding values of nigellidine, EGCG and TFDG to ACE2 are presented in supplementary file, S-table2.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, a study revealed that EGCg inhibited angiotensin-converting enzyme (ACE) activity through oxidative conversion into quinone and successive covalent binding of the quinone to ACE. ( 11 ) Furthermore, the paper revealed that EGCg is a non-competitive inhibitor of ACE and EGCg binds to a specific site but not the active site of ACE.…”
Section: Biological Effect Of Quinone On Cells/tissuesmentioning
confidence: 96%
“…( 9 , 10 , 18 ) Tea has beneficial effects on human health and it has been speculated that these effects are caused by the components in tea. The quinone of EGCg could participate in some of the biological activities of tea; ( 11 ) we discuss the mechanisms behind this in section 3 below. Flavonoid-derived quinones, such as quercetin quinone, might be key players in the induction of cell protection against oxidative stress.…”
Section: Generation Of Quinones and Reaction Toward Biomoleculesmentioning
confidence: 99%
See 1 more Smart Citation